Household survey on attitude and practice toward dengue infection among rural dwellers - Hamfadi, Nur Shafikah; Rasudin, Nur Syahmina; Abdul Ghafar, Noraini (International Journal Of Community Medicine And Public Health, 2019)
Background: Dengue fever is the most important mosquito-borne disease that has rapidly spread in tropical regions of the world in recent years. Due to absence of vaccine, the only method available is to prevent and control dengue is by preventing transmission of the disease. However, the control needs support, cooperation and participation from community. The objective of this study is to assess the current level of knowledge, attitude and practice toward dengue fever among the community living in rural area, beside to ascertain the association between those three domains, and to evaluate the effect of sociodemographic factors toward them. Methods: A cross sectional survey was performed among 202 respondents dwelling in rural area, whom were selected through stratified random sampling. Knowledge, attitude, and practice toward dengue fever were assessed through a set of self-administered validated questionnaire. Results: The community had moderate level of knowledge (64.4%), positive attitude (79.7%), and good level of practices (65.3%) on dengue fever. Television was the main source of information on dengue fever (76.2%). From the result, there were significant association between level of education with practice on dengue fever (p=0.001). The result also shown that there was significant association between knowledge and practice in the community (p=0.008). Conclusions: More health education programmes should be organized to increase knowledge and help the translation of knowledge into practice of prevention.